Sketch2Cartoon: Composing Cartoon Images by Sketching - Wang, Changhu; Zhang, Jun; Yang, Bruce; Zhang, Lei (ACM Multimedia, 2011)
In this paper, we introduce the Sketch2Cartoon system, which is an automatic cartoon making system by leveraging a novel sketch-based clipart image search engine. Different from existing work, most of which either limited users to the pre-prepared characters or only used keyword queries to search materials, Sketch2Cartoon enables users to sketch major curves of characters and props in their mind, and real-time search results from millions of clipart images could be selected to compose the cartoon images. The selected components are vectorized and thus could be further edited. By enabling sketch-based input, the cartoon image making process becomes more natural, and even a child who is too young to read or write can draw whatever he/she imagines and get interesting cartoon images.